PENGEMBANGAN BAHAN AJAR MATA KULIAH UMUM BAHASA INDONESIA SEBAGAI SUPLEMEN - Lesi Anggraini (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2022)
The purpose of this study is to develop (1) teaching materials needed by students; (2) developing the design of teaching materials needed by students; and (3) obtaining the effectiveness of teaching materials. The method of this research is Researh and Deveploment (R&D. Data obtained by observation, interview, documentation and questionnaire techniques. Subjects in this study were conducted to a team of experts and students. Results of this research development was conducted in the first phase with a needs analysis that includes (1) availability and the suitability of available teaching materials is inadequate, (2) knowing the supplement of teaching materials needed by lecturers and students, (3) the importance of presenting teaching materials with the objectives achieved, and (4) the use of language that is easily understood but in accordance with language rules. The second stage, the development of ingredients as a supplement which includes (1) the title of teaching material, (2) the suitability of the form and content of the teaching material supplement being developed, and (3) the structure of the teaching material supplement. by using the realibility test (r).